Social Class Reflected In Frances Hodgson Burnett's A Little Princess Novel (1904): A Marxist Approach - DWI SULISTYOWATI, ENDAH; , Titis Setyabudi, S.S. M.Hum (2016)
This study is proposed to reveal how social class is reflected in A Little Princess (1904) novel by Francess Hodgon Burnett. The objectives of this study are to describe social class in Frances Hudson Burnett's A Little Princess (1904). The researcher employs qualitative research. The researcher uses two data sources: primary and secondary data source. The primary data source is about the novel itself. Then the secondary data are taken from other sources which are related to the primary data such as the literary books, dictionary, and some articles related to the novel and website about A Little Princess novel. The technique of data collection is library research. The technique of analyzing data is descriptive qualitative. Based on Marxist analysis, social class can be shown from first, A Litlle Princess novel wants to describe Sara Crewe as wealthy, polite, smart young girl. Second, A Little Princess novel wants to reflect that inequality of social class happened in a Miss Minchin boarding school. From the research, social class is devided into three classes, they are upper class, middle class, and working class.